(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
It is known that synonyms are one of the tools that serve to increase the richness of speech and its effectiveness. Appropriate use of synonyms increases the effectiveness and brightness of the speech. On the contrary, their inappropriate and aimless use creates nonsense in the speech. This paper widely presents synonymous features of lexical units denoting emotional state in English and Uzbek languages